The Coral Sea 1942 : the first carrier battle - Stille, Mark.; White, John (Illustrator) (Oxford : Osprey, 2009)
The Battle of the Coral Sea is unique in the annals of naval history. It is the first battle in which enemy fleets never came within sight of one another. Instead, aircraft launched from carrier decks were sent out to attack the enemy with bombs and torpedoes. In May of 1942, the Japanese fleet moved on Port Moresby, the last Allied base between Australia and Japan. Forced to respond, the Americans sent two aircraft carriers to protect the base. In the ensuing battle, one American carrier was destroyed and the other severely damaged. However, the Japanese also lost a carrier and decided to withdraw. Although bloody, it proved to be an important strategic victory for the Allies as the Japanese were forced to attempt future attacks on Port Moresby over land. Using the latest research and numerous period photographs, retired USN Commander Mark O Stille tells the story of this important and unique battle in the Pacific War.
Origins of the campaign -- Chronology -- Opposing Commanders: The IJN ; The US Navy -- Opposing Fleets: The IJN carrier force ; The US Navy carrier force ; Orders of battle -- Opposing plans: The Japanese plan: The Naval General Staff vs the Combined Fleet ; The American plan -- The Battle of the Coral Sea: Opposing moves ; The American carrier raid on May 4 ; Movement to contact: May 5-6 ; The clashes of May 7 ; Death of a carrier ; Pre-battle preparations: May 8 ; The American strike on the MO Carrier Striking Force ; The Japanese strike TF-17 ; After the strikes ; the accounting -- The aftermath.
Includes bibliographical references and index.
Keywords: 1942; Geschichte; Coral Sea, Battle of the, 1942.; Bataille de la mer de Corail, 1942.; Coral Sea, Battle of the, 1942.; World War, 1939-1945 -- Campaigns -- Pacific Ocean; Pacific Ocean -- Coral Sea; Korallensee -- Seeschlacht; Nonfiction